Assessing insurance claims as a measure for outpatient antimicrobial stewardship - Mariana M. Lanata; Jacob T. Kilgore; Brandi Holthaus; Jonathan M. Willis; Tess Anderson; Borden Samples; Jennifer Sparks; Joseph E. Evans; Bethany A. Wattles; Michael J. Smith (Antimicrobial Stewardship & Healthcare Epidemiology, 2025)
Abstract